Cyclical occupational choice in a model with rational wage expectations and perfect occupational mobility - Bernhard Felderer; André Drost (Institute for Advanced Studies (IHS), 2000)
In many professional labor markets the number of new workers follows a cyclical time path. This phenomenon is usually explained by means of a cobweb model that is based on the assumptions of myopic wage expectations and occupational immobility. Since both assumptions are questioned by the empirical literature, we develop an alternative model that is based on the assumptions of rational wage expectations and perfect occupational mobility. Depending on the production function, the model can generate cycles in the number of workers who enter a professional labor market.
Keywords: I21; J44; 330; occupational choice; rational expectations; occupational mobility; linear dynamics; Berufswahl; Arbeitsmobilität; Rationale Erwartung; Theorie